2009
DOI: 10.1016/j.actpsy.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

One, two, three, many – Subitizing in active touch

Abstract: a b s t r a c t 'Subitizing' refers to rapid and accurate judgement of small numbers of items, while response times and error rates increase rapidly for larger set-sizes. Most enumeration studies have been done in vision. Enumeration studies in touch have mostly involved 'passive touch', i.e. touch without active exploration. In daily life a much more common situation is that of 'active touch', e.g. when we count the number of coins in our pocket. To investigate numerosity judgement in active touch, we let sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 41 publications
8
63
0
Order By: Relevance
“…Moreover, the three groups of participants presented similarly accurate and fast performance [|ER| and log(CV)] within the subitizing range. Therefore, our data clearly demonstrate that subitizing is a general perceptual mechanism that extends beyond visual to tactile (Plaisier et al, 2009a) and auditory (Camos & Tillmann, 2008) stimuli. They also allow us to rule out the possibility that participants in the original Riggs et al (2006) study enumerated the number of fingers stimulated within the subitizing range using visual information, since sighted-blindfolded participants performed similarly to sighted-seeing participants for small array sizes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, the three groups of participants presented similarly accurate and fast performance [|ER| and log(CV)] within the subitizing range. Therefore, our data clearly demonstrate that subitizing is a general perceptual mechanism that extends beyond visual to tactile (Plaisier et al, 2009a) and auditory (Camos & Tillmann, 2008) stimuli. They also allow us to rule out the possibility that participants in the original Riggs et al (2006) study enumerated the number of fingers stimulated within the subitizing range using visual information, since sighted-blindfolded participants performed similarly to sighted-seeing participants for small array sizes.…”
Section: Discussionsupporting
confidence: 62%
“…Riggs et al's results are of theoretical importance because they suggest that subitizing is a general perceptual process, not one restricted to the visual modality. Similar results were recently replicated in active touch by Plaisier, Bergmann Tiest, and Kappers (2009a) and in the auditory domain by Camos and Tillmann (2008).…”
supporting
confidence: 80%
“…However, non-visual stimuli have been often used as well. Non-verbal numerical abilities in our species have been reported with both auditory (Agrillo et al, 2010b;Lipton and Spelke, 2003) and tactile (Krause et al, 2013;Plaisier et al, 2009) stimuli with apparently no difference in number acuity across the sensory modalities involved (Feigenson, 2007). Concerning nonhuman primates, chimpanzees (Pan troglodytes) were shown to compare auditory quantities in a way that closely resembled how they compared visual quantities (Beran, 2012).…”
Section: Introductionsupporting
confidence: 54%
“…2006; Plaisier et al. 2009). The finding that subitizing occurs in touch is particularly interesting because it has been shown that parieto-frontal brain circuits dedicated to number processing partially overlap with those dedicated to hand and finger movements (Pinel et al.…”
Section: Introductionmentioning
confidence: 99%